Non-genetic Effects and Genetic Parameters Estimation on Growth Traits of Indonesian Etawah Grade Goats - Nugroho, A. R.; Sumantri, C.; Sutanto, A.; Ulum, M. F.; Gunawan, A. (Tropical Animal Science Journal, 2026)
Growth traits are important determinants of the efficiency and productivity of goat production systems. The Etawah Grade (EG) goat is a local Indonesian breed that is used for both milk and meat production. This study aimed to analyze the influence of non-genetic factors, estimate genetic parameters, and assess long-term genetic progress in growth traits of the EG goat at different ages. A total of 17,783 body weight records from 523 sires and 4342 dams were used to analyze non-genetic effects and estimate genetic parameters for growth traits in EG goats. The effect of non-genetic factors (sex, parity, season, year, and type of birth) on growth traits (body weight and average daily gain) was analyzed using a general linear model (GLM). Heritability and genetic trend were estimated using restricted maximum likelihood (REML) in the BreedR package from the R program. The results of this study showed that sex, parity, season, year, and type of birth had significant effects (p